Confirmation of the presence of Ochlerotatus (RMstlcoidus) quasirusticus (Torres canamares) in the Iberian Peninsula, and the first record from the Madrid region. Issue 13 (2002) - Salom, R Melero-A1cibarand F.
No abstract available